InP/InGaAs double heterojunction bipolar transistors with BVCEO = 12 V and fmax = 470 GHz. Issue 8 (1st April 2015) - Kashio, N.; Kurishima, K.; Ida, M.; Matsuzaki, H.
Abstract : 0.25 μm emitter InP/InGaAs double heterojunction bipolar transistors (DHBTs) are presented that simultaneously exhibit a high collector current density ( J c ) of more than 3 mA/μm 2 and high breakdown voltage (BVCEO ) of 12 V. The DHBTs consist of a 30 nm‐thick InGaAs base, 250 nm‐thick InGaAs/InAlGaAs/InP collector and 150 nm‐thick n ‐doped InP field buffer. Since the doping level of the InP field buffer is relatively high, only the InGaAs/InAlGaAs/InP collector is depleted at low V CE . Thus, the DHBTs can provide f t = 173 GHz and f max = 470 GHz at J c = 3.5 mA/μm 2 . On the other hand, at a high V CE, both the InGaAs/InAlGaAs/InP collector and InP field buffer are depleted. Therefore, the effective depletion thickness increases, which results in a BVCEO of 12 V. These results indicate that the use of the InP field buffer provides both high‐speed performance and high BVCEO .